Breakdown of the few-level approximation in collective systems - Evers, J; Kiffner, M; Keitel, C (Optical Society of America, 2007)
In contrast to single atoms, in collective systems, the vacuum couples transitions with orthogonal dipole moments. This leads to a geometry-dependent dynamics and to a breakdown of the few-level approximation in collective systems. © 2007 Optical Society of America.